Solid-state electrolyte and lithium-ion battery

CN117878389BActive Publication Date: 2026-10-23QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311821958.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2026-10-23
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

[0004]但卤化物固态电解质在长期使用中可能会发生结构变化或相变,导致电解质性能下降,此外,卤化物固态电解质与金属锂负极的电化学稳定性较差,容易在固态电池循环中发生副反应,进而造成固态电解质结构破坏、循环稳定性降低等问题

Benefits of technology

[0023]本申请通过在卤化物固态电解质,尤其是氯化物固态电解质内制造缺锂环境,以及调控组分及比例,以及价态配合等调节手段协同作用,制备晶体结构稳定,无序化程度高的固态电解质,使得制备的氯化物固态电解质的离子电导率大于1.8 mS*cm-1,耐高压性能优良,与正负极兼容性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117878389B_ABST
    Figure CN117878389B_ABST
Patent Text Reader

Abstract

The application relates to a solid-state electrolyte and a lithium ion battery. The solid-state electrolyte comprises a halide solid-state electrolyte, the chemical general formula of the halide solid-state electrolyte is Li 2+a‑c‑2d A a B b C c D d X6, 2+a-c-2d<2, 0.1<=c+d<=0.5, c+2d>a, wherein 0.01<=a<=0.4, 0.1<=b<=0.6, 0<c<=0.5, 0<d<=0.5, 0.1<=c+d<=0.5, c+2d>a. The solid-state electrolyte is prepared by mixing raw materials and ball milling, and the preparation method is simple. Meanwhile, the solid-state electrolyte has highly disordered ion distribution and lithium vacancies, the crystal structure is loose, the ion transmission and moving speed are improved, the ion conductivity of the electrolyte is improved, and the initial efficiency, capacity and other performances of the prepared lithium ion battery are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a solid electrolyte and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries are the primary energy storage devices in portable electronic devices, electric vehicles, and energy storage systems. Through development and improvement, the energy density, power density, battery capacity, and cycle life of lithium-ion batteries have significantly improved, expanding their application areas and increasing demand, which in turn places higher demands on their performance. Solid-state electrolytes, as one of the core factors affecting lithium-ion battery performance, have received widespread attention due to their superior safety profile, as they do not contain flammable organic solvents.

[0003] Solid electrolytes include oxide solid electrolytes, polymer solid electrolytes, glassy solid electrolytes, and halide solid electrolytes. While oxide solid electrolytes possess high ionic conductivity and stability, their preparation and processing are complex, and they exhibit high impedance. Polymer solid electrolytes offer superior mechanical flexibility and lower impedance, but they are sensitive to temperature and humidity, exhibit poor high-temperature stability, and have short cycle lives. Glassy solid electrolytes possess high ionic conductivity and excellent mechanical and chemical stability, but their preparation and processing are challenging. Halide solid electrolytes have attracted widespread attention due to their high ionic conductivity and good interfacial compatibility.

[0004] However, halide solid electrolytes may undergo structural changes or phase transitions during long-term use, leading to a decline in electrolyte performance. Furthermore, halide solid electrolytes exhibit poor electrochemical stability with lithium metal anodes, making them prone to side reactions during solid-state battery cycling, which can result in structural damage and reduced cycle stability. Therefore, developing halide solid electrolyte materials with good structural stability and superior ionic conductivity is an urgent problem to be solved. Summary of the Invention

[0005] Therefore, in view of the above problems, this application provides a solid electrolyte and a lithium-ion battery to solve the above technical problems.

[0006] The first aspect of this application provides a solid electrolyte, including a halide solid electrolyte, wherein the chemical formula of the halide solid electrolyte is Li. 2+a-c-2d A a B b C c D d X6,

[0007] Furthermore, 2+ac-2d<2, 0.1≤c+d≤0.5, c+2d>a; where 0.01≤a≤0.4, 0.1≤b≤0.6, 0<c≤0.5, 0<d≤0.5; A, B, C, and D are all at least one metallic element; X is a halogen element.

[0008] In some implementations, the total number N of the element types of elements A and B satisfies 3 ≤ N ≤ 10.

[0009] In some embodiments, the ionic conductivity λ of the solid electrolyte satisfies: λ ≥ 1.8 mS·cm -1 .

[0010] In some implementations, b > a.

[0011] In some embodiments, element C has a pentavalent valence; element D has a hexavalent valence; element A has a trivalent valence; and element B has a tetravalent valence.

[0012] In some embodiments, element C includes Mo; element D includes W.

[0013] In some embodiments, element A includes at least one of Fe, Al, Sc, V, Ga, Y, Ru, Rh, In, Bi, Au, Ir, Re, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; and element B includes at least one of Zr, Ti, Ge, Sn, Te, Pt, and Hf.

[0014] In some embodiments, element X is at least one halogen element.

[0015] In some embodiments, element X is chlorine.

[0016] The second aspect of this application provides a method for preparing a halide solid electrolyte, comprising the following steps:

[0017] Weigh the precursor LiX and the halides AX, BX, CX, and DX corresponding to the metal elements A, B, C, and D according to the stoichiometric ratio of the general formula. Add them to the ball mill jar in the glove box, along with the corresponding proportion of grinding beads, and seal the container.

[0018] The ball mill jar was placed in a high-energy ball mill and ball milled to obtain a composite solid electrolyte.

[0019] In some implementations, the molar ratio of LiX, AX, BX, CX, and DX is 2+ac-2d: a:b:c:d.

[0020] In some implementations, 2 + ac - 2d < 2, 0.1 ≤ c + d ≤ 0.5, c + 2d > a, where 0.01 ≤ a ≤ 0.4, 0.1 ≤ b ≤ 0.6, 0 < c ≤ 0.5, and 0 < d ≤ 0.5. Preferably, b > a.

[0021] A third aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, and a solid electrolyte membrane.

[0022] In some embodiments, the solid electrolyte membrane comprises the solid electrolyte provided in the first aspect described above.

[0023] This application utilizes a combination of methods, including creating a lithium-deficient environment within halide solid electrolytes, particularly chloride solid electrolytes, and adjusting the composition, ratio, and valence state coordination, to prepare solid electrolytes with stable crystal structures and high degrees of disorder. This results in chloride solid electrolytes with an ionic conductivity greater than 1.8 mS*cm. -1 It has excellent high voltage resistance and good compatibility with positive and negative electrodes. Attached Figure Description

[0024] Figure 1 This is the X-ray diffraction pattern of the solid electrolyte of Example 1 of this application. Detailed Implementation

[0025] A detailed reference is now provided to embodiments of this application, one or more of which are described below. Each embodiment is provided for explanation and not for limitation. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.

[0026] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.

[0027] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0028] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0029] In this article, when referring to units for data ranges, if the unit is only followed by the right endpoint, it means that the units for the left and right endpoints are the same. For example, 100~150 nm means that the units for the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0030] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0031] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0032] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0033] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0034] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0035] Existing halide solid electrolytes are prone to deliquescence in air, which is not conducive to packaging, transportation and use. At the same time, the ionic conductivity of halide solid electrolytes decreases significantly after deliquescence, resulting in a decline in cycle performance. Therefore, this application provides a composite solid electrolyte to solve the above-mentioned technical problems.

[0036] The first aspect of this application provides a solid electrolyte, including a halide solid electrolyte, wherein the general chemical formula of the halide solid electrolyte is Li. 2+a-c-2d A a B b C c D d X6,

[0037] Furthermore, 2+ac-2d<2, 0.1≤c+d≤0.5, c+2d>a, where 0.01≤a≤0.4, 0.1≤b≤0.6, 0<c≤0.5, and 0<d≤0.5.

[0038] In some implementations, 2+ac-2d<2; 2+ac-2d includes, but is not limited to, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, and 1.8; preferably, 2+ac-2d<1.8; more preferably, 2+ac-2d<1.6.

[0039] This application utilizes the preparation of lithium-deficient halide solid electrolytes, which improves the disorder and amorphization of solid electrolytes, thereby effectively enhancing their ionic conductivity. Lithium vacancies provide more ion conduction channels, allowing lithium ions to move more easily in solid ion conductors, thus improving ionic conductivity. Furthermore, lithium vacancies can be used for lithium ion storage and release, improving the stability of the crystal structure.

[0040] In some implementations, 0.1 ≤ c + d ≤ 0.5; c + d includes, but is not limited to, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, and 0.5; preferably, 0.15 ≤ c + d ≤ 0.4; more preferably, 0.2 ≤ c + d ≤ 0.3.

[0041] In some embodiments, 0.01≤a≤0.4, where a includes, but is not limited to, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, and 0.4; preferably, 0.05≤a≤0.4; more preferably, 0.01≤a≤0.3.

[0042] In some implementations, 0.1≤b≤0.6, including but not limited to 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, and 0.6; preferably, 0.2≤a≤0.5; more preferably, 0.3≤a≤0.4.

[0043] In some implementations, 0 < c ≤ 0.5, including but not limited to 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, and 0.5; preferably, 0.05 ≤ a ≤ 0.3; more preferably, 0.1 ≤ a ≤ 0.2.

[0044] In some implementations, 0 < d ≤ 0.5, including but not limited to 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, and 0.5; preferably, 0.05 ≤ a ≤ 0.3; more preferably, 0.1 ≤ a ≤ 0.2.

[0045] In some implementations, the total number of element types of element A and / or element B is ≥3.

[0046] As one implementation method, element A includes ≥3 types of metals, and element B includes ≥3 types of metals.

[0047] In one implementation, element A includes ≥3 types of metals, and element B includes ≤3 types of metals.

[0048] In one implementation, element A includes ≤3 types of metals, and element B includes ≥3 types of metals.

[0049] As one implementation, element A includes ≤3 types of metals, element B includes ≤3 types of metals, but the sum of the types of metals included in element A and element B is ≥3.

[0050] In some implementations, the total number of element types of element A and element B satisfies 3≤N≤10; including but not limited to 3, 4, 5, 6, 7, 8, 9, and 10.

[0051] In some implementations, the total number of element types for elements A and B is 3 ≤ N ≤ 6.

[0052] In some embodiments, the ionic conductivity λ of the solid electrolyte satisfies: λ ≥ 1.8 mS*cm -1 Preferably, the ionic conductivity λ of the solid electrolyte satisfies: λ ≥ 2.0 mS*cm -1 .

[0053] In some implementations, b > a.

[0054] In some implementations, element C has a pentavalent valence; element D has a hexavalent valence; element A has a trivalent valence; and element B has a tetravalent valence.

[0055] In some embodiments, element C includes Mo; element D includes W; element A includes at least one of Fe, Al, Sc, V, Ga, Y, Ru, Rh, In, Bi, Au, Ir, Re, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; and element B includes at least one of Zr, Ti, Ge, Sn, Te, Pt, and Hf.

[0056] In some embodiments, element X is at least one halogen element. Preferably, element X is chlorine.

[0057] This application obtains a halide solid electrolyte with a high degree of amorphization by selecting and limiting the types and quantities of main elements and other elements in the halide electrolyte, as well as by controlling the valence state and number of atoms of the elements.

[0058] It is understood that the main element B used in this application has high ionic conductivity, which can provide a good ion transport pathway in solid ionic conductors, thereby promoting the rapid movement of ions and realizing an efficient ion conduction process; at the same time, it has high chemical stability, which can work stably in electrolytes for a long time and improve the stability of electrolytes; in addition, the main element B has a high melting point and thermal stability, as well as rich crystal structures, which can more flexibly realize the control of material structure and performance.

[0059] The lithium-deficient solid electrolyte provided in this application offers more ion conduction channels, facilitating the movement of lithium ions within the solid ion conductor. This allows lithium ions to effectively hop within the crystal structure, thereby improving ionic conductivity. Furthermore, the positively charged lithium vacancies can balance the charge with surrounding negative ions, preventing charge accumulation. Additionally, the lithium vacancies provided in this application can be used for lithium ion storage and release, enhancing the stability of the crystal structure.

[0060] The high-valence elements used in this application have smaller ionic radii and higher charge densities, which can promote ion migration in solid structures, enhance ion transport rates, and further improve ion conduction performance. In addition, high-valence elements can expand the electrochemical window of the electrolyte, allowing for a higher potential range and providing higher voltage and energy storage capacity.

[0061] The second aspect of this application provides a method for preparing a halide solid electrolyte, comprising the following steps:

[0062] S1: Weigh the precursor LiX and the halides AX, BX, CX, and DX corresponding to the metal elements A, B, C, and D according to the stoichiometric ratio of the general formula, add them to the ball mill jar in the glove box, add the corresponding proportion of ball milling beads, and seal.

[0063] S2: Place the ball milling jar into a high-energy ball mill and ball mill to obtain a composite solid electrolyte.

[0064] In step S1, the molar ratio of LiX, AX, BX, CX, and DX is 2+ac-2d: a:b:c:d, where 2+ac-2d < 2, 0.01 ≤ a ≤ 0.4, 0.1 ≤ b ≤ 0.6, 0 < c ≤ 0.5, 0 < d ≤ 0.5, 0.1 ≤ c+d ≤ 0.5, and c+2d > a. Preferably, b > a.

[0065] This application does not limit the material of the grinding jar and grinding beads. Any grinding jar and grinding beads that can be used in the preparation of the first halide solid electrolyte can be used in this application. For example, the grinding jar and grinding beads are both made of zirconium dioxide.

[0066] In some embodiments, the corresponding ratio refers to the mass ratio of grinding balls to raw materials being (15:1) to (60:1); the raw materials refer to the precursor LiX and the halides AX, BX, CX, and DX corresponding to the metal elements A, B, C, and D. The mass ratio of grinding balls to raw materials includes, but is not limited to, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, and 60:1; preferably, the mass ratio of grinding balls to raw materials is (15:1) to (30:1).

[0067] In some embodiments, the rotational speed of the ball milling device is 300 rpm to 700 rpm; including but not limited to 300 rpm, 320 rpm, 350 rpm, 380 rpm, 400 rpm, 420 rpm, 450 rpm, 480 rpm, 500 rpm, 520 rpm, 550 rpm, 580 rpm, 600 rpm, 620 rpm, 650 rpm, 680 rpm, and 700 rpm; preferably, the rotational speed of the ball milling device is 350 rpm to 500 rpm; more preferably, the rotational speed of the ball milling device is 450 rpm to 500 rpm. The ball milling time is 6h to 48h, including but not limited to 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 46h, and 48h; preferably, the ball milling time is 12h to 47h; more preferably, the ball milling time is 30h to 45h.

[0068] A third aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, and a solid electrolyte membrane.

[0069] In some embodiments, the solid electrolyte membrane comprises the solid electrolyte provided in the first aspect described above.

[0070] In some embodiments, the positive electrode includes a positive electrode plate and the negative electrode includes a negative electrode plate, wherein a positive electrode tab is led out on the positive electrode plate and a negative electrode tab is led out on the negative electrode plate.

[0071] The positive electrode includes a positive current collector and a positive active electrode material layer formed on the current collector, and the negative electrode includes a negative current collector and a negative active electrode material layer formed on the negative current collector. The positive active electrode material layer includes a positive active material, a positive binder, and a positive conductive material. The positive active material is a compound capable of reversibly inserting and deintercalating lithium. Specifically, the positive active material includes one or a combination of at least two of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium nickel manganese oxide, lithium-rich manganese-based materials, lithium vanadium phosphate, and ternary materials (lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide).

[0072] Preferably, the mass percentage of the positive electrode active material contained in the positive electrode active material layer can be 80wt% to 99wt%, such as 80wt%, 82wt%, 85wt%, 87wt%, 90wt%, 92wt%, 95wt%, 97wt%, 99wt%, etc., and preferably 92wt% to 98.5wt%.

[0073] The positive electrode binder is used to bond the positive electrode active material, the positive electrode conductive material, and the positive electrode current collector together. Specifically, the positive electrode binder may contain at least one selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber, preferably polyvinylidene fluoride.

[0074] The mass percentage of the positive electrode binder contained in the positive electrode active electrode material layer can be 1wt% to 20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt% to 10wt%.

[0075] The positive electrode conductive material is mainly used to assist and improve the conductivity in secondary batteries, and there are no particular limitations on it in the embodiments of this application, as long as it is conductive and does not cause chemical changes. Specifically, the positive electrode conductive material may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal cracking black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the perspective of improving conductivity, the positive electrode conductive material is preferably carbon black.

[0076] The specific surface area of ​​the positive electrode conductive material can be 80m². 2 / g~200 m 2 / g, preferably 100 m 2 / g~150 m 2 / g.

[0077] The mass percentage of positive conductive material contained in the positive active electrode material layer can be 1wt% to 20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt% to 10wt%.

[0078] The thickness of the positive electrode active electrode material layer can be 30μm to 400μm, for example 30μm, 40μm, 50μm, 80μm, 110μm, 200μm, 300μm, 400μm, preferably 50μm to 110μm.

[0079] The positive electrode sheet can be manufactured by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and rolling. The positive electrode slurry includes a solvent and positive electrode active material and / or positive electrode binder and positive electrode conductive material dissolved in the solvent.

[0080] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and the amount used may be such that a preferred viscosity is obtained when the positive electrode active material is included and, selectively, a positive electrode binder, a positive electrode conductive material, etc. are included. For example, the amount of solvent included in the positive electrode slurry may be such that the concentration of the solids containing the positive electrode active material and, selectively, the positive electrode binder and the positive electrode conductive material is 50 wt% to 95 wt%, preferably 70 wt% to 90 wt%.

[0081] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises at least a negative electrode active material and a negative electrode binder.

[0082] The negative electrode active material in this application embodiment is not particularly limited, as long as it is a substance that can electrochemically adsorb and release s-region metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions, such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These substances can be used alone, or two or more can be used in combination.

[0083] In some embodiments, carbon materials can be selected as the negative electrode active material, specifically one or more of the following: graphite, needle coke, amorphous carbon, carbon-containing mesophase, carbon fiber, and carbon materials with low graphitization. Graphite can include natural graphite, artificial graphite, etc. Alternatively, materials obtained by coating these materials with carbon materials, such as amorphous carbon or graphitides, can also be used. Amorphous carbon includes, but is not limited to, particles obtained by sintering a monolithic mesophase, and particles obtained by sintering a carbon precursor after infusible treatment. Examples of carbonaceous particles with low graphitization include particles obtained by sintering organic matter at temperatures typically below 2500°C.

[0084] In addition, non-metallic materials that can be used as negative electrode active materials include elemental silicon and its compounds, such as Si and SiOx (0≤x<2). Since silicon-containing materials are prone to expansion and easy to fall off from the negative electrode current collector, and have poor conductivity, they are often used in combination with carbon materials, such as core-shell structures containing carbon coating layers.

[0085] In some embodiments, elemental metals and metal compounds may also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.

[0086] The mass percentage of the negative electrode active material contained in the negative electrode active material layer can be 80 wt% to 99 wt%, for example, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 97 wt%, 99 wt%, etc., preferably 95 wt% to 97 wt%.

[0087] When the negative electrode active material is a non-metallic material such as carbon material, the negative electrode binder can be a water-based binder, such as sodium carboxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymers, cyclodextrin, or one or more of these.

[0088] The negative electrode active material layer can be obtained by coating a negative electrode slurry onto a negative electrode current collector and then performing operations such as drying. The negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When using an aqueous solvent as the liquid medium for forming the negative electrode slurry, it is preferable to use a thickener for slurry formation. Thickeners are generally used to adjust the viscosity of the slurry.

[0089] The thickener in the embodiments of this application may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts, etc.

[0090] The mass percentage of thickener in the negative electrode slurry can be 0.1wt% to 5wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., preferably 0.5wt% to 3wt%, and more preferably 0.6wt% to 2wt%.

[0091] It should be noted that in the embodiments of this application, the positive electrode active material layer and / or the negative electrode active material layer may also be formed by dry pressing without the use of a binder. There is no limitation here, and users can set it according to their actual needs.

[0092] In some embodiments, the solid electrolyte membrane is formed by loading the solid electrolyte of the first aspect into a mold and pressing it into a sheet.

[0093] In some embodiments, the solid electrolyte membrane is formed by mixing the solid electrolyte of the first aspect described above with a binder to obtain a mixture, and then rolling the mixture to form a solid electrolyte membrane.

[0094] In some embodiments, the mass ratio of solid electrolyte to binder is (80~99):(1~20); including but not limited to 80:20, 85:15, 90:10, 95:5, 99:1; preferably, the mass ratio of solid electrolyte to binder is (85~95):(5~15); more preferably, the mass ratio of solid electrolyte to binder is (85~95):(85~95).

[0095] It is understood that the mixing process includes methods such as ball milling, air mixing, or pulverizing. In this application, the method of mixing is not particularly limited, and any known mixing method can be used without departing from the inventive concept of this application. Preferably, a pulverizer is used for mixing.

[0096] It is understood that this application does not specifically limit the type of adhesive, and any known adhesive can be used in this application without departing from the inventive concept. The examples provided are merely illustrative and not intended to limit the scope of protection of this application. Adhesives include, but are not limited to, one or more of the following: polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride hexafluoropropylene (PVDF-HFP), polypropylene (PP), polyethylene (PE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid compounds, polyacrylonitrile, and sodium alginate.

[0097] In some embodiments, the halide solid electrolyte powder and binder can be directly placed into a device that provides shear force, and fibrosis can be completed during continuous mixing. Under the action of shear force, the binder transforms from a powder state into fibers, which are uniformly distributed between the particles of the halide electrolyte powder, forming a binder-bridged halide electrolyte powder structure. In this embodiment, the binder includes a fibrous binder, which means that the binder can transform from a powder state to a fibrous state under the action of shear force. Preferably, the fibrous binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.

[0098] In other embodiments of this example, the binder may also include a non-fibrous binder, which, for example, may be styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyacrylic acid binders, etc. Generally, non-fibrous binders play a supplementary bonding role in the mixed system, increasing the adhesion to halide solid electrolyte powder particles and improving the mechanical properties of the solid electrolyte membrane.

[0099] The present application will be further described below with reference to specific embodiments and comparative examples.

[0100] Example 1

[0101] This embodiment provides a solid electrolyte: including a halide solid electrolyte Li 1.9 Dy 0.1 In 0.1 Bi 0.1 Zr 0.4 Mo 0.2 W 0.1 Cl6.

[0102] This embodiment provides a method for preparing a solid electrolyte:

[0103] S1: According to the stoichiometric ratio, LiCl, ACl3, BCl4, CCl5, and DCl6 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d)::a:b:c:d. Add the appropriate proportion of grinding balls and seal the container.

[0104] Element A includes Dy, In, and Bi; element B is Zr; element C is Mo; element D is W; element X is Cl; a is 0.3; b is 0.4; c is 0.2; and d is 0.1. Therefore, the molar ratio is 1.9:0.3:0.4:0.2:0.1. The mass ratio of the milled beads to the total amount of LiCl, ACl3, BCl4, CCl5, and DCl6 is 30:1.

[0105] S2: Place the ball milling jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely Li. 1.9 Dy 0.1 In 0.1 Bi 0.1 Zr 0.4 Mo 0.2 W 0.1 Cl6 powder. The room temperature ionic conductivity of the resulting solid electrolyte powder is 1.836 mS / cm.

[0106] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0107] The solid electrolyte membrane includes the solid electrolyte prepared above. The solid electrolyte membrane is prepared by loading the solid electrolyte into a mold and pressing it into a sheet to form a solid electrolyte membrane with a thickness of 20 μm.

[0108] Example 2

[0109] This embodiment provides a solid electrolyte: including a halide solid electrolyte Li 1.9 Dy 0.1 In 0.1 Bi0.1 Zr 0.2 Ti 0.1 Sn 0.1 Mo 0.2 W 0.1 Cl6. That is, there are 3 types of element A and 3 types of element B.

[0110] This embodiment provides a method for preparing a solid electrolyte:

[0111] S1: According to the stoichiometric ratio, LiCl, ACl3, BCl4, CCl5, and DCl6 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d):a:b:c:d. Add the appropriate proportion of grinding balls and seal the container.

[0112] Element A includes Dy, In, and Bi; element B includes Zr, Ti, and Sn; element C is Mo; element D is W; and element X is Cl. The molar ratios are: a = 0.3, b = 0.4, c = 0.2, and d = 0.1. Therefore, the molar ratio is 1.9:0.3:0.4:0.2:0.1. The mass ratio of the milled beads to the total amount of LiCl, ACl3, BCl4, CCl5, and DCl6 is 30:1.

[0113] S2: Place the ball mill jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely, Li. 1.9 Dy 0.1 In 0.1 Bi 0.1 Zr 0.2 Ti 0.1 Sn 0.1 Mo 0.2 W 0.1 Cl6 powder; the room temperature ionic conductivity of the resulting solid electrolyte powder is 2.113 mS / cm.

[0114] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0115] The solid electrolyte membrane includes the solid electrolyte prepared above. The solid electrolyte membrane is prepared by loading the solid electrolyte into a mold and pressing it into a sheet to form a solid electrolyte membrane with a thickness of 20 μm.

[0116] Example 3

[0117] This embodiment provides a solid electrolyte: including a halide solid electrolyte Li 1.9 Dy 0.2 In 0.1 Zr 0.4 Mo0. 2W 0.1 Cl6. That is, there are three types of elements A and B.

[0118] This embodiment provides a method for preparing a solid electrolyte:

[0119] S1: According to the stoichiometric ratio, LiCl, ACl3, BCl4, CCl5, and DCl6 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d): a:b:c:d. Add the appropriate proportion of grinding balls and seal the container.

[0120] Element A includes Dy, In, and Bi; element B includes Zr, Ti, and Sn; element C is Mo; element D is W; and element X is Cl. The molar ratios are: a = 0.3, b = 0.4, c = 0.2, and d = 0.1. Therefore, the molar ratio is 1.9:0.3:0.4:0.2:0.1. The mass ratio of the milled beads to the total amount of LiCl, ACl3, BCl4, CCl5, and DCl6 is 30:1.

[0121] S2: Place the ball mill jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely, Li. 1.9 Dy 0.2 In 0.1 Zr 0.4 Mo 0.2 W 0.1 Cl6 powder; the room temperature ionic conductivity of the resulting solid electrolyte powder is 1.945 mS / cm.

[0122] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0123] The solid electrolyte membrane includes the solid electrolyte prepared above. The solid electrolyte membrane is prepared by loading the solid electrolyte into a mold and pressing it into a sheet to form a solid electrolyte membrane with a thickness of 20 μm.

[0124] Comparative Example 1

[0125] Provide a solid electrolyte: including a halide solid electrolyte Li 1.9 Dy 0.3 Zr 0.4 Mo 0.2 W 0.1 Cl6. This means it does not contain high entropy; compared to Example 3, this comparative example lacks the element In.

[0126] A method for preparing a solid electrolyte is provided:

[0127] S1: According to the stoichiometric ratio, LiCl, ACl3, BCl4, CCl5, and DCl6 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d): a:b:c:d. Add the appropriate proportion of grinding balls and seal the container.

[0128] Element A includes Dy; element B is Zr; element C is Mo; element D is W; element X is Cl; a is 0.3; b is 0.4; c is 0.2; d is 0.1, therefore, the molar ratio is 1.9:0.3:0.4:0.2:0.1. The mass ratio of the ball mill beads to the total amount of LiCl, ACl3, BCl4, CCl5, and DCl6 is 30:1.

[0129] S2: Place the ball mill jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely, Li. 1.9 Zr 0.4 Dy 0.3 Mo 0.2 W 0.1 Cl6 powder; the room temperature ionic conductivity of the resulting solid electrolyte powder is 0.852 mS / cm.

[0130] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0131] The solid electrolyte membrane includes the solid electrolyte prepared above. The solid electrolyte membrane is prepared by loading the solid electrolyte into a mold and pressing it into a sheet to form a solid electrolyte membrane with a thickness of 20 μm.

[0132] Comparative Example 2

[0133] This embodiment provides a solid electrolyte: including a halide solid electrolyte Li 2.6 Dy 0.2 In 0.2 Bi 0.2 Zr 0.2 Ti 0.1 Sn 0.1 Cl6 means that no molybdenum or tungsten was added, and no high-valence elements were added.

[0134] This embodiment provides a method for preparing a solid electrolyte:

[0135] S1: According to the stoichiometric ratio, LiCl, ACl3, and BCl4 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d):a:b, and the corresponding proportion of grinding balls are added and the container is sealed.

[0136] Element A includes Dy, In, and Bi; element B includes Zr, Ti, and Sn; a is 0.6; b is 0.4; therefore, the molar ratio is 2.6:0.6:0.4. The mass ratio of the total amount of milled beads to LiCl, ACl3, and BCl4 is 30:1.

[0137] S2: Place the ball mill jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely, Li 2.6 Zr 0.2 Ti 0.1 Sn 0.1 Dy 0.2 In 0.2 Bi 0.2 Cl6 powder; the room temperature ionic conductivity of the resulting solid electrolyte powder is 1.121 mS / cm.

[0138] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0139] The solid electrolyte membrane includes the solid electrolyte prepared above. The solid electrolyte membrane is prepared by loading the solid electrolyte into a mold and pressing it into a sheet to form a solid electrolyte membrane with a thickness of 20 μm.

[0140] Comparative Example 3

[0141] This embodiment provides a solid electrolyte: including a halide solid electrolyte Li 2.1 Dy 0.2 In 0.1 Bi 0.1 Zr 0.4 Mo 0.1 W 0.1 Cl6. That is, (2+ac-2d)>2, which is not a lithium-deficient state.

[0142] This embodiment provides a method for preparing a solid electrolyte:

[0143] S1: According to the stoichiometric ratio, LiCl, ACl3, BCl4, CCl5, and DCl6 are added to the ball mill jar in the glove box in a molar ratio of (2+ac-2d): a:b:c:d. Add the appropriate proportion of grinding balls and seal the container.

[0144] Element A includes Dy, In, and Bi; element B is Zr; element C is Mo; element D is W; element X is Cl; a is 0.4; b is 0.4; c is 0.1; d is 0.1, therefore, the molar ratio is 2.1:0.4:0.4:0.1:0.1. The mass ratio of the ball mill beads to the total amount of LiCl, ACl3, BCl4, CCl5, and DCl6 is 30:1.

[0145] S2: Place the ball mill jar into a high-energy ball mill and ball mill at 500 rpm for 45 hours to obtain solid electrolyte powder, namely, Li. 2.1 Zr 0.4 Dy 0.2 In 0.1 Bi 0.1 Mo 0.1 W 0.1 Cl6 powder; the room temperature ionic conductivity of the resulting solid electrolyte powder is 1.384 mS / cm.

[0146] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0147] The solid electrolyte membrane includes the solid electrolyte prepared above. The preparation method of the solid electrolyte membrane is as follows: the solid electrolyte is mixed with the binder PVDF to obtain a mixture, the mixture is loaded into a mold and pressed into a sheet to form a solid electrolyte membrane; the membrane thickness is 20 μm.

[0148] Comparative Example 4

[0149] The preparation method of the halide electrolyte Li₂ZrCl₆ (LZC) is as follows:

[0150] Weigh LiCl and ZrCl4 at a molar ratio of 2:1, mix them, and add them to a ball mill jar. Mill the mixture at 500 r / min for 6 h, using a ball milling ratio of 30:1 to the raw materials, to form the halide solid electrolyte Li2ZrCl6. The room temperature ionic conductivity of the obtained halide solid electrolyte powder is 0.36 mS / cm.

[0151] A lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The positive electrode includes a positive electrode active material, LiCoO2; the negative electrode includes graphite.

[0152] The solid electrolyte membrane includes the solid electrolyte prepared above. The preparation method of the solid electrolyte membrane is as follows: the solid electrolyte is mixed with the binder PVDF to obtain a mixture, the mixture is loaded into a mold and pressed into a sheet to form a solid electrolyte membrane; the membrane thickness is 20 μm.

[0153] Test case

[0154] (1) Characterization of halide solid electrolytes by XRD and other methods

[0155] The halide solid electrolyte prepared in Example 1 and the existing halide electrolyte LZC (Comparative Example 4) were analyzed using XRD diffraction. The results are as follows: Figure 1As shown in the figure, compared with ordinary halide electrolyte LZC, the electrolyte prepared in this application has lower crystallinity and lower overall peak intensity of each characteristic peak, indicating an increased degree of disorder in the crystal.

[0156] from Figure 1 As can be seen from the characteristic peaks, the halide solid electrolyte powder material synthesized in the examples has a uniform elemental distribution.

[0157] (2) Initial discharge capacity and first-effect test

[0158] The lithium-ion batteries of the examples and comparative examples were subjected to charge-discharge tests at 60°C, 0.1C charge-discharge, and charge-discharge cutoff voltage of 4.2V-3.0V. The first charge-discharge efficiency and first discharge capacity of the batteries were recorded, and the results are shown in Table 1.

[0159] (3) Ionic conductivity test

[0160] At room temperature, the halide solid electrolyte membranes obtained in the examples and comparative examples were connected to an electrochemical workstation for initial impedance testing. The final ionic conductivity was calculated using the formula σ = I / (AR), and the data are summarized in Table 1. Where σ is the conductivity in S / cm, I is the average thickness of the halide solid electrolyte membrane in cm, and A is the area of ​​the halide solid electrolyte membrane in cm². 2 R is the bulk impedance of the halide solid electrolyte membrane, in Ω.

[0161] Table 1

[0162]

[0163] As shown in Table 1, in Comparative Example 3, the ionic conductivity is significantly reduced in the non-lithium-deficient state. Simultaneously, the initial efficiency and battery capacity decrease. This is because, in the non-lithium-deficient state, no lithium vacancies are provided, restricting the free movement of lithium ions and leading to a decrease in ionic conductivity. Comparative Example 2 lacks high-valence elements. High-valence elements, due to their smaller ionic radii and higher charge densities, can promote lithium ion migration and further improve the ionic conductivity of the halide solid electrolyte. Omitting high-valence elements slows down the migration rate of lithium ions, thus affecting the ionic conductivity and the initial efficiency and battery capacity of the prepared battery. Comparative Example 1 did not use three or more elements A and B. In this case, the ionic conductivity decreased, and the initial efficiency and battery capacity of the prepared battery also decreased significantly.

[0164] This application obtains a high-entropy solid electrolyte containing lithium vacancies by limiting the types, valence states, and combinations of elements contained in the halide solid electrolyte. At the same time, by using host elements with higher ion transport pathways and rich crystal structures, the ion transport rate is further improved. Combined with the introduction of high-valence elements, the migration of ions in the solid structure is promoted, thereby improving the first efficiency and battery capacity of the prepared battery.

[0165] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0166] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A solid electrolyte, characterized in that, The solid electrolyte includes a halide solid electrolyte with the general chemical formula Li. 2+a-c-2d A a B b C c D d X6, And, 2+ac-2d<2, 0.1≤c+d≤0.5, c+2d>a; Wherein, 0.01≤a≤0.4, 0.1≤b≤0.6, 0<c≤0.5, 0<d≤0.5; A, B, C, and D are all metallic elements; X is a halogen element. The total number of element types N of elements A and B satisfies 3 ≤ N ≤ 10; Element C has a pentavalent valence; element D has a hexavalent valence. Element C includes Mo; element D includes W; Element A includes at least one of Fe, Al, Sc, V, Ga, Y, Ru, Rh, In, Bi, Au, Ir, Re, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; element B includes at least one of Zr, Ti, Ge, Sn, Te, Pt, and Hf.

2. The solid electrolyte according to claim 1, characterized in that, The ionic conductivity λ of the solid electrolyte satisfies: λ ≥ 1.8 mS·cm -1 .

3. The solid electrolyte according to claim 1, characterized in that, b > a.

4. The solid electrolyte according to claim 1, characterized in that, Element A has a trivalent valence; element B has a tetravalent valence.

5. The solid electrolyte according to claim 1, characterized in that, Element X is at least one halogen element.

6. The solid electrolyte according to claim 5, characterized in that, Element X is chlorine.

7. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane; The solid electrolyte membrane includes the solid electrolyte as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • High-entropy halide solid electrolyte material and preparation method and application thereof

    CN115332618A

  • Solid electrolyte material, preparation method and electrode

    CN116315052A